PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL DISCOVERY LEARNING PADA MATERI PIKTOGRAM KELAS IV SD NEGERI 21 PARAK KOPI - Welianti, Risa; Engreini, Syofianti; Hendri, Sherlyane; Suciana, Fadila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of fourth-grade students in Mathematics at SD Negeri 21 Parak Kopi, Padang City. The problem was caused by the limited use of varied learning models, teacher-centered instruction, and the lack of student involvement in learning activities. As a result, students were less active, had difficulty understanding mathematical concepts, and many failed to achieve the established Learning Objective Achievement Criteria (KKTP). This study aimed to describe the improvement of students’ learning outcomes through the implementation of the Discovery Learning model. The research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. It was conducted in three cycles consisting of planning, implementation, observation, and reflection stages. The subjects were one teacher and 25 fourth-grade students of SD Negeri 21 Parak Kopi, Padang City, during the second semester of the 2025/2026 academic year. Data were collected through observation, tests, and documentation. The findings showed continuous improvement in each cycle. The lesson planning score increased from 78.12% in Cycle I to 90.62% in Cycle II and 96.87% in Cycle III. Teacher activities improved from 78.57% to 92.85%, while student activities increased from 75.00% to 85.71%. Students’ learning outcomes also improved from 72.4% in Cycle I to 82.4% in Cycle II and 91.4% in Cycle III. Therefore, the Discovery Learning model was effective in improving students’ learning outcomes in Mathematics.